2016
DOI: 10.1186/s12888-016-1098-9
|View full text |Cite
|
Sign up to set email alerts
|

The cross-interaction between global and age-comparative self-rated health on depressive symptoms–considering both the individual and combined effects

Abstract: BackgroundNumerous studies suggesting the relation between self-rated health (SRH) and depression have been reported using different measures. Therefore, we attempted to determine the difference in a depressive scale based on the different ways of measuring health between global SRH (SRH-global) and age-comparative SRH (SRH-age). Then, the combined effect of SRH-global and SRH-age on depressive symptoms was further investigated.MethodsData from the Korean Longitudinal Study of Ageing (KLoSA) from 2008 to 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Study 2 used data from wave 6 of the Korean Longitudinal Study of Aging (KLoSA) conducted by the Korea Labor Institute in 2016. The design and data collection procedures of the KLoSA study are described elsewhere [13,22] Among the participants, we selected 5687 who reported their marital status as 'married' and who provided information on our variables of interest (life satisfaction, spousal satisfaction, monthly household income, education, and age). Perceived overall spousal satisfaction with the relationship was measured by individual participants' answers to the question, "How satisfied are you with the relationship with your spouse?…”
Section: Study 2 Satisfaction With Spousal Relationship Household Imentioning
confidence: 99%
“…Study 2 used data from wave 6 of the Korean Longitudinal Study of Aging (KLoSA) conducted by the Korea Labor Institute in 2016. The design and data collection procedures of the KLoSA study are described elsewhere [13,22] Among the participants, we selected 5687 who reported their marital status as 'married' and who provided information on our variables of interest (life satisfaction, spousal satisfaction, monthly household income, education, and age). Perceived overall spousal satisfaction with the relationship was measured by individual participants' answers to the question, "How satisfied are you with the relationship with your spouse?…”
Section: Study 2 Satisfaction With Spousal Relationship Household Imentioning
confidence: 99%
“…The CES‐D was created in 1977 by Radloff 32 . The scale is well known and remains one of the most widely used instruments in the field of psychiatric epidemiology 33,34 . We used the CES‐D‐10 Korean edition for measuring depressive symptoms defined by the American Psychiatric Association's Diagnostic and Statistical Manual (DSM‐IV).…”
Section: Methodsmentioning
confidence: 99%
“…32 The scale is well known and remains one of the most widely used instruments in the field of psychiatric epidemiology. 33,34 We used the CES-D-10 Korean edition for measuring depressive symptoms defined by the American Psychiatric Association's Diagnostic and Statistical Manual (DSM-IV). The total score of the measure ranges from zero to 30; the lower the score, the better the depression symptoms.…”
Section: Depression Score (Ces-d)mentioning
confidence: 99%
“…The CESD was created in 1977 by Radloff [17]. The scale is well known and remains one of the most widely used instruments in the field of psychiatric epidemiology [18,19]. We used the CESD-10 Korean edition for measuring depressive symptoms defined by the American Psychiatric Association' Diagnostic and Statistical Manual (DSM-IV).…”
Section: Center For Epidemiologic Studies Depression Scale (Cesd)mentioning
confidence: 99%